JIPEN (DENDA ADAT): ALTERNATIF UNTUK MEMINIMALISIR PERCERAIAN DI MASYARAKAT DAYAK KALIMANTAN TENGAH - Maimunah Maimunah (Belom Bahadat, 2020)
This article is motivated by the prevalence of divorce in the community. One of them is motivated by the disagreement over the pre-marriage agreement that was agreed upon before the marriage took place. Even though in essence there is a marriage agreement with the aim of maintaining the sustainability of the household and also to maintain the commitment in the marriage itself. The rules regarding this marriage agreement also apply in Central Kalimantan. Jipen (customary fine) is applied to married couples who decide to divorce. This is still being implemented with the aim of minimizing the divorce rate, especially for the Dayak tribe. This article uses a library research method using book reviews and references from journals that discuss pre-marriage agreements and customary fines in marriage. The conclusion is that the enactment of jipen in the Dayak customary community is a policy of the damang (customary leader) to minimize the high divorce rate and give high respect for the sacred value of marriage as a commitment to maintaining the integrity of the household and its enforcement in the legal system in Indonesia does not violate and also in accordance with the demands of Religion which views marriage as a sacred bond that must be properly maintained by both partners.